Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil - Ott, Ricardo; Rodrigues, Everton Nei Lopes (Zootaxa, 2017)
The araneid genus Larinia Simon currently includes 56 species, eleven of them with New World distribution (World Spider Catalog, 2016). North American species of the genus were revised first time by Levi (1975) and South American species by Harrod et al. (1991). According to these authors there are four species known from subtropical South America (Larinia bivittata Keyserling 1885; L. montecarlo (Levi, 1988); L. t-notata (Tullgren, 1905); L. tucuman Harrod, Levi & Leibensperger, 1991) and also four species known from tropical South America (L. ambo Harrod, Levi & Leibensperger, 1991; L. directa (Hentz, 1847); L. lampa Harrod, Levi & Leibensperger, 1991; L. neblina Harrod, Levi & Leibensperger, 1991). According to Buckup et al. (2010) a total of 209 species of Araneidae are recorded for state of Rio Grande do Sul, including the three species L. bivittata, L. montecarlo and L. t-notata.